FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN KONTRASEPSI IMPLANT DI PUSKESMAS BAUMATA - asyah nur (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2022)
The government's policy on family planning according to the BKKBN currently leads to the use of the Long-Term Contraceptive Method (MKJP). The implant contraceptive device is one of the most effective contraceptives and its use is prioritized with an effectiveness of 0.2-1 pregnancy failure per 100 women. Factors that influence the use of contraceptives include partner factors, namely age, lifestyle, desired family size, experience with previous contraception, socio-culture, husband's attitude and support, health factors, namely health status, menstrual history, family history. The purpose of this study was to analyze the socio-cultural factors, knowledge, and husband's support related to the use of contraceptive implants at the Baumata Health Center. The research design used was a cross sectional study. The population in this study were all mothers who used implant contraceptives at the Baumata Health Center. While the sample in this study were some mothers who used contraceptive implants at the Baumata Health Center. The sampling technique is purposive sampling. Data collection using primary and secondary data. The tool to collect data at the time of the research was a questionnaire sheet. Analysis of the data used is univariate, bivariate and then tested using the Chi Square test. The results of the study concluded that there was no relationship between maternal social culture and the use of contraceptive implants at Baumata Health Center with p > = 0.05, there was a relationship between mother's knowledge and use of implant contraceptives at Baumata Health Center with p value < = 0.05 , and there is a relationship between husband and mother's support with the use of implant contraceptives at Baumata Health Center with p < = 0.05. Keywords: Socio-Cultural, Knowledge, Husband's Support, Implant Contraception